1994
DOI: 10.1111/j.1745-6606.1994.tb00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Communication Patterns and Marketplace Motivations, Attitudes, and Behaviors of Children and Mothers

Abstract: This study examined the relation between family communication patterns (FCP) and mothers' marketplace motivations, attitudes, and behaviors (MAB). Adolescents' prediction accuracy of mothers' consumption motivations was also investigated. Results indicate mothers' materialistic and shopping tendencies, advertising attitudes, information use, and consumption motivations are linked to FCP. Adolescents' predictions of mothers' consumption motivations coincided with mothers' self‐reported motivations. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 24 publications
1
75
0
2
Order By: Relevance
“…Researchers have studied how family communication, in terms of its frequency, pattern, and content, influence various socialization outcomes, such as the development of marketplace skills and values in children and adolescents (e.g., Carlson, Walsh, Laczniak, & Grosbart, 1994;Moschis, 1985;Moschis & Moore, 1984;Moschis, Moore, & Smith, 1983). However, research explicitly examining the role of family communication in the similarity between parents and their postadolescent offspring regarding preferences and consumption orientations is limited.…”
Section: Factors Affecting Intergenerational Influencementioning
confidence: 99%
“…Researchers have studied how family communication, in terms of its frequency, pattern, and content, influence various socialization outcomes, such as the development of marketplace skills and values in children and adolescents (e.g., Carlson, Walsh, Laczniak, & Grosbart, 1994;Moschis, 1985;Moschis & Moore, 1984;Moschis, Moore, & Smith, 1983). However, research explicitly examining the role of family communication in the similarity between parents and their postadolescent offspring regarding preferences and consumption orientations is limited.…”
Section: Factors Affecting Intergenerational Influencementioning
confidence: 99%
“…Contemporary children are also increasingly growing up in nontraditional family structures (Dotson & Hyatt, 2000;Neeley, 2005) and moving between numerous social contexts within the course of their daily lives (Corsaro, 2003;Corsaro & Eder, 1990). Although parents, especially mothers, are consistently identified as primary socialization agents (Carlson et al, 1994), others have argued that peers play an equal role in children's socialization (e.g., Youniss, 1980). As young children spend increasing amounts of time interacting with peers, whether in informal (e.g., play dates, at the playground) or formal settings (e.g., daycare, school, athletics), it becomes necessary for socialization models to account for peer culture influence, the associated social practices and artifacts, and the resultant tensions that may arise between adult-and peer-oriented socialization messages.…”
Section: Models Of Consumer Socialization and The Very Youngmentioning
confidence: 99%
“…For example, researchers have observed young children and their parents in retail environments (Ironico, 2012; Kinsky & Bichard, 2011), yet if researchers are interested in the home environment, then they could spend extended periods of time with children and families in their homes (Kerrane, Hogg, & Bettany, 2012). Similarly, although studies have consistently shown that parents have a great influence on children's consumer socialization, particularly through communication styles and parental mediation (Buijzen & Mens, 2007;Carlson, Walsh, Laczniak, & Grossbart, 1994;Dotson & Hyatt, 2005;Nathanson, 1999Nathanson, , 2002Nathanson & Botta, 2003), the structure and nature of "family" and the people in and around the home have changed in the past 30 years [e.g., single-parent families, extended family child-rearing, delayed marriage, and child-rearing; (Flurry, 2007)]. Given changes in home-life and media-life, it is time to observe consumer socialization in today's child's home environment.…”
mentioning
confidence: 99%
“…In fact, many recent research studies have analyzed how parents and/or peers influence the consumption attitudes of individual consumers (Bush, Smith, and Martin, 1999;Carlson, Walsh, Laczniak, and Grossbart, 1994;Keillor, Parker, and Schaefer, 1996;Laczniak, Muehling, and Carlson, 1995). …”
Section: Consumer Socializationmentioning
confidence: 99%